Revealing the shear band origin of white etching area in rolling contact fatigue of bearing steel - Su, Yun-Shuai; Li, Shu-Xin; Yu, Feng; Lu, Si-Yuan; Wang, Yong-Gang (International journal of fatigue, 2021)
•Shear band does not have to adiabatic as it can form under quasi static loading.•White etching area and shear band are suggested to be shear localization.•Phase transformation to austenite is observed in white etching area and shear band.•Shear localization occurs at a large micro strain of estimated 0.5–0.8 in white etching area. White etching area (WEA) has become a big challenge for bearing failure under rolling contact fatigue. Despite of the extensive investigations, the origin of the WEA has not yet been well understood. This work attempts to elucidate the origin based on a new perspective that both the WEA and the shear band (SB) can be the common responses under shear plastic deformation in bearing steel, rather than the unique phenomenon in rolling contact fatigue. First, the SB is generated under quasi-static compression loading, indicating that the SB does not necessarily have to be adiabatic and is not limited to high strain rate loading. Second, the WEA is produced under rolling contact fatigue. The SB is compared with the WEA in terms of shear localization, microstructures, formation mechanism and crack development. The results suggest that both the SB and the WEA can be regarded as the shear localization under large plastic deformation. The SB consists of either nanocrystallines or well-developed equiaxed grains with transformed austenite. The WEA consists of either nanocrystallines or a mixed structure of amorphous phase and nanocrystallines with transformed austenite. Connecting the WEA with the SB provides a new insight into interpreting the origin and formation mechanism of the WEA, and help the further understanding of bearing failure under rolling contact fatigue.